MEKANISME KINERJA LEMBAGA OMBUDSMAN REPUBLIK INDONESIA PERWAKILAN PROVINSI RIAU (MEKANISME PENAGGANAN LAPORAN MASYARAKAT DI KOTA PEKANBARU ) - Tarahesti Wulandari; Zulkifli Zulkifli (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2017)
Public Service is any form of service in the form of public goods or services which in principle become the responsibility and implemented by government agencies. The Ombudsman is the institution that oversees the public service. This study aims to determine the performance mechanism of the Ombudsman Institution of the Republic of Indonesia Representative of Riau Province in tackling the community report in Pekanbaru City. Indicators Assessment of community reporting subscription mechanisms used include written clarification, field investigations, summons and recommendations / suggestions. The type of research located in the office of the Ombudsman of the Republic of Indonesia Representative of Riau Province in Pekanbaru City is a descriptive survey, which prioritizes the list of questionnaires as a means of collecting data and data collected with this tool and then used as the main raw material to analyze the empirical conditions and objectivity of objectives research objectives at the location of conscientious. There are 2 population groups and the sample in this research is Ombudsman Member (Assistant Ombudsman) which amounts to 5 people and people in Pekanbaru City which amounted to 79 people. The sample size assigned from both groups is 84 people. wo sampling techniques used in assigning individual samples are census techniques for the Ombudsman Assistants of the Republic of Indonesia Riau Province Representative and incidental techniques for community groups. Types and data collection techniques used consisted of primary data collected by using questionnaire and interview techniques and secondary data collected using observation technique techniques. While the data analysis technique used is to use the tool table frequency. Based on this analytical technique the researchers assessed and concluded that the mechanism of handling reports by the Ombudsman Ombudsman of the Republic of Indonesia Representative of Riau Province in Pekanbaru City is at interval is quite done.